Measuring incremental burdens associated with increasing preventive-treatment failures among adults with migraine: a retrospective, cross-sectional study - Jessica Ailani; Nemin Chen; Avani Patel; Nathan Spence; Nikoletta Sternbach; Katie B. Tellor; Motomori Lewis; Joshua Brown (Therapeutic Advances in Neurological Disorders)
Background: Migraine inflicts substantial personal, social, and economic tolls on many adults in the United States (US). Acute and preventive medicines can offer some relief, but most patients are untreated or experience treatment failures. How preventive-treatment failures affect outcomes for patients no longer on preventive treatments or for patients with migraine is insufficiently understood. Objective: To measure the patient-reported health and economic burdens associated with increasing preventive-treatment failures among US adults with diagnosed migraine. Design: Retrospective, cross-sectional study. Methods: Data analyzed were from the 2023 US National Health and Wellness Survey. Participants were adults diagnosed with migraine, having ≥4 monthly migraine or headache days, having taken acute or preventive prescription migraine medications or currently taking acute prescription migraine medications, and taking no preventive migraine medications. Participants were categorized as never treated with preventive medicines, having failed 1 preventive medicine, or having failed ≥2 preventive medicines. Health-related quality of life (HRQoL) was assessed with the Migraine Disability Assessment, RAND’s 36-Item Short Form Survey Instrument, 5-Level EuroQoL instrument (EQ-5D), Work Productivity and Activity Impairment General Health version, 9-Item Patient Health Questionnaire, and 7-Item Generalized Anxiety Disorder scale. Details about medication use and health care resource use (HCRU) were collected. Data were adjusted by inverse probability of treatment weighting and compared using two-sided two-sample t -tests or Chi-square tests. Results: Patients who had failed preventive treatments had poorer HRQoL, greater work productivity loss, greater nonwork activity impairment, and greater HCRU than patients who had never taken preventive treatments. The number of preventive-treatment failures scaled with disease burden. Patients with ≥2 treatment failures had significantly lower EQ-5D scores (0.69 vs 0.73) than those for prevention-naïve patients; patients with ≥2 treatment failures had significantly higher overall work productivity loss (45.9% vs 34.9%), activity impairment (46.8% vs 36.7%), and higher rates of emergency room visits (37.0% vs 25.2%), hospitalization (23.5% vs 12.3%), and neurologist visits (17.6 vs 10.9%) than those of prevention-naïve patients. Medication overuse rates were similar among patients with any treatment failures and prevention-naïve patients (migraine-specific: 34.4%-39.3%; overall: 59.2%-62.3%). Conclusion: US adults with frequent migraines who failed preventive treatments have significantly greater unmet needs and different acute medication use patterns than adults who never took treatments.